Peripheral monocytes and soluble biomarkers in autoimmune encephalitis. Issue 135 (February 2023) - Wesselingh, Robb; Griffith, Sarah; Broadley, James; Tarlinton, David; Buzzard, Katherine; Seneviratne, Udaya; Butzkueven, Helmut; O'Brien, Terence J.; Monif, Mastura
Abstract: Background and objectives: Autoimmune encephalitis (AE) is an inflammatory disease of the central nervous system which can result in long-term seizures and cognitive dysfunction despite treatment with immunotherapy. The role of the innate immune system in AE is not well established. To investigate the contribution of innate immunity to AE and its long-term outcomes we evaluated peripheral monocytes and serum cytokines in the periphery of patients with AE. Methods and results: We recruited 40 patients with previously diagnosed AE and 28 healthy volunteers to our cross-sectional observation study and evaluated their peripheral blood monocytes via flow cytometry and serum cytokines (CCL-2, CCL-17, G-CSF, GM-CSF, IFNγ, IL-1α, IL-1β, IL-2, IL-4, IL-5, IL-6, IL-10, IL-17, TNFα) via ELISA.Compared with controls the AE cohort had expansion of the 'pro-inflammatory' CD14 + CD16 + monocyte sub-population (7.13% vs 5.46%, p < 0.01) with higher levels of serum IL-6 (2.34 pg/mL vs 0.54 pg/mL, p < 0.001). These changes were most significant in anti -LGI-1 antibody mediated AE, an AE subtype with poor long-term cognitive outcomes. Conclusion: Expansion of the peripheral CD14 + CD16 + monocyte population and increased serum IL-6 in AE is reflective of changes seen in other systemic inflammatory and neurodegenerative conditions. These changes may indicate a persistent pro-inflammatory state in AE and may contribute to poor long-term outcomes. Highlights: Pro-inflammatory peripheral monocytes are increased in autoimmune encephalitis. IL-6 is also elevated in the serum despite treatment with immunotherapy. Changes in inflammatory biomarkers are most marked in the LGI-1 autoimmune encephalitis subset.